USE OF ACTIVE CONSUMERS FOR BALANCE OF ELECTRICITY IN THE ELECTRIC GRID - LEZHNIUK, PETRO; KOZACHUK, OLEG; GALUZINSKIY, OLEKSANDER (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article considers the problem of balancing power and electricity in an electric grid, in which electricity consumption and its generation by renewable energy sources (RES) are commensurable to each other. Some of the electricity consumers in the electric grid are active, which are traditionally used to level load schedules at a multi-rate tariff. The development of RES in electric grids changes the conditions of their operation and poses new tasks. Electric grids with a significant amount of RES in the balance of power and electricity have all the signs of a local electric system (LES) with characteristic problems. In particular, this concerns the instability of the generation of wind and photovoltaic power plants (WPP, PV), the creation of a system of ways and means of reserving RES for reliable and high-quality electricity supply, regulation of electricity parameters in accordance with standards, ensuring self-organization and self-recovery as necessary elements of Smart Grid technologies, etc. It is shown that, first of all, in order to compensate for the instability of RES generation, it is recommended to use the possibilities of coordination in the electric grid of electricity generation and consumption schedules by active consumers. It is advisable to use other methods and means for full balancing of the amount of electricity that remained unbalanced after such reconciliation: available maneuverable power system capacities, electrochemical storage devices, hydrogen produced in the grid. Comprehensive coordination of generation and consumption schedules in the electrical grid for balancing electricity in it is carried out using a morphometric method, which is based on the transition from the Cartesian to the polar coordinate system.